Evaluasi Penggunaan Obat Anti Hipertensi Pada Pasien Stroke Iskemik Di Rsud Arifin Achmad Tahun 2022 - Nawwar Irfan; Nursyafni; Ayu Rahmawati; Mestika, Diani (LPPM, Universitas Muhammadiyah Riau, 2023)
Antihypertensive drugs are one of the drugs most commonly given to ischemic stroke patients. Ischemic stroke is a stroke resulting from thrombosis or embolism that occurs in the cerebral blood vessels and causes obstruction of cerebral blood flow to the cerebral blood vessels. The use of drugs is rational if the patient receives treatment according to his clinical needs. The aim of this study was to determine the appropriate use of antihypertensive drugs in ischemic stroke patients based on the right indication, selection of the right drug, right dose and determine the relationship between sociodemographics and the results of antihypertensive treatment in ischemic stroke patients at Arifin Achmad Regional Hospital. The method used in this research is a descriptive observational method using retrospective data which was carried out by recording medical record data of patients with a final diagnosis of ischemic stroke accompanied by hypertension with a sample size of 80 patients. people (52.5%), 45-64 years old 44 people (55%), working patients 53 people (66.3%), and the most widely used drug class was amlodipine as many as 67 people (56.8%). In the results of the chi-square test with a significance value of p value = 0.05 for the relationship between age and gender on risk factors, the age value was p = 0.004, while the gender value was p = 0.014. It was concluded that the evaluation of the use of antihypertensive drugs at Arifin Achmad Hospital was 100% correct and showed that age and risk factors were related, and gender and risk factors were related. Keywords: Hypertension, ischemic stroke, evaluation of drug use